1997
DOI: 10.1097/00005176-199707000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Can the Histologic Changes of Cystic Fibrosis-Associated Hepatobiliary Disease be Predicted by Clinical Criteria?

Abstract: Significant histologic liver disease is common in cystic fibrosis, although the exact nature of the lesion cannot be predicted without liver biopsy. A clinical liver score that was developed for this may be useful in determining which patients require more definitive evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 14 publications
4
49
0
5
Order By: Relevance
“…7), indicating that patients with liver disease might be missed by a too liberal definition of pathological liver enzyme levels used by other investigators. 6,28 Although the diagnostic accuracy is increased by a liver biopsy, this has been questioned in patients with CF owing to the focal character of the liver disease. 8 However, a more recent study showed good agreement between needle and wedge biopsies even in patients with CF, 28 and repeated needle biopsies in individual patients have shown similar morphology over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7), indicating that patients with liver disease might be missed by a too liberal definition of pathological liver enzyme levels used by other investigators. 6,28 Although the diagnostic accuracy is increased by a liver biopsy, this has been questioned in patients with CF owing to the focal character of the liver disease. 8 However, a more recent study showed good agreement between needle and wedge biopsies even in patients with CF, 28 and repeated needle biopsies in individual patients have shown similar morphology over time.…”
Section: Discussionmentioning
confidence: 99%
“…6,28 Although the diagnostic accuracy is increased by a liver biopsy, this has been questioned in patients with CF owing to the focal character of the liver disease. 8 However, a more recent study showed good agreement between needle and wedge biopsies even in patients with CF, 28 and repeated needle biopsies in individual patients have shown similar morphology over time. 19,20 These studies suggest that liver biopsies might be as valuable in patients with CF as in patients with other liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, as in the two patients reported here, the clinical and biological abnormalities associated with focal biliary cirrhosis are mild [38]. Hepatomegaly, as observed in the two cases reported here, is present in only 30 to 43% of patients at diagnosis [1].…”
Section: Discussionmentioning
confidence: 75%
“…Although liver biopsy has been considered as the gold standard for assessing stage and grade of most chronic liver diseases, recently more noninvasive tests have been investigated (19). Potter et al have described a clinical score including clinical factors and liver enzymes to predict the type of liver disease in CF with a sensitivity of 85% and a specificity of 82%, whereas its score did not evaluated US abnormality (20). It seems that by delineation of the liver architecture by US, the prevalence of liver disease in children with CF will be augmented.…”
Section: Discussionmentioning
confidence: 99%